Case Report: Cavernous hemangioma of rib: an extremely rare venous malformation but easily misdiagnosed as aggressive tumors - Liu, Shan; Xiang, Luan; Ding, Fan; Yuan, Ling; Wang, Xiu-Mei (Frontiers in Oncology, 2023)
Hemangioma is a congenital vascular malformation that occurs commonly in the skin and soft tissues of younger individuals but rarely in the bone. The term hemangioma occurring in bone has been referred to as venous bony malformation also. In these rare cases, vertebral bodies occur more often, followed by the craniofacial skeleton and long bones. Most rib tumors are malignant, and hemangiomas of the rib tend to grow expansively and disrupt the cortex. Venous malformations in ribs are not tumors but can be misdiagnosed as aggressive tumors or infectious processes. In fact, hemangioma of bone is a locally aggressive benign vascular malformation associated with a good prognosis. To date, no more than 50 cases of rib hemangiomas have been described in the English literature. This report presents a case of an asymptomatic 27-year-old female patient who found a quail egg-sized lump on the right side of her chest that was the size of a cocoon two months prior. Then, the lump grew rapidly to the size of an egg when she came to the hospital. Because of its worrisome histomorphology features and aggressive clinical radiologic findings, it was once misdiagnosed as a malignant tumor by most doctors. However, the pathological results after the operation confirmed rib hemangioma. Therefore, this case report aims to share this particular case so that more doctors can better understand the particularity of this disease progression.